(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present research identifies the factors affecting the public relations identification in the organizational structure of the ministries such as Jihad Agriculture, Communications and Oil. After identifying the factors, they were summarized in three groups of social trust, organizational loyalty, increasing customer knowledge. The research method used in this descriptive research was correlation and using the calculated correlation coefficients, a structural model was compiled. The statistical population of the present research included managers, experts and specialists of public relations units of the mentioned ministries in 2020 and the sample size was selected based on Cochran’s formula equivalent to 186 people. Necessary information was collected through four questionnaires of Cheney’s organizational identity, social trust, customer knowledge management, and organizational loyalty. The analysis of test information was also done in the two categories of descriptive and inferential, the main results of which are as follows: Based on the results, it was.